Severe Dental Disease as a Presenting Sign of Relapsed 6q24-Related Transient Neonatal Diabetes Mellitus - Anna Delamerced; Lauren J. Massingham; Jose Bernardo Quintos (Case Reports in Endocrinology)
Transient neonatal diabetes mellitus (TNDM) is a rare form of diabetes that presents in infancy and is characterized by intrauterine growth restriction and hyperglycemia without ketones on urinalysis. Patients are treated with insulin until remission, usually within the first year. Relapse to a permanent state may occur later in life, with a mean age of 14 years. The most common cause of TNDM is a chromosome 6q24 mutation that affects pancreatic β-cell function. Reports of relapse have been limited. We describe a case of an adolescent female with TNDM due to 6q24 hypomethylation who relapsed at 15 years of age with severe dental disease as the presenting sign.